2008
DOI: 10.1631/jzus.b0820049
|View full text |Cite
|
Sign up to set email alerts
|

The value of endoscopic ultrasonography on diagnosis and treatment of esophageal hamartoma

Abstract: EUS was superior to other imaging means in diagnosis and treatment of hamartoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
7
1
1
Order By: Relevance
“…In our case EUS was not usable because of very proximal location of the tumour in the oesophagus but CT scan revealed cystic nature of the tumour and the tumour appeared benign in nature. In contrast to our finding Zhang et al have reported usefulness of EUS in the differential diagnosis of cervical oesophageal hamartomas (8).There are a few reports on successful endoscopic treatments of oesophageal hamartomas (5,16,17). According to Ginai et al a prerequisite for successful endoscopic ligation of the hamartoma is that it is pediculated (15).…”
contrasting
confidence: 94%
See 1 more Smart Citation
“…In our case EUS was not usable because of very proximal location of the tumour in the oesophagus but CT scan revealed cystic nature of the tumour and the tumour appeared benign in nature. In contrast to our finding Zhang et al have reported usefulness of EUS in the differential diagnosis of cervical oesophageal hamartomas (8).There are a few reports on successful endoscopic treatments of oesophageal hamartomas (5,16,17). According to Ginai et al a prerequisite for successful endoscopic ligation of the hamartoma is that it is pediculated (15).…”
contrasting
confidence: 94%
“…There are a few reports on successful endoscopic treatments of oesophageal hamartomas (5,16,17). According to Ginai et al a prerequisite for successful endoscopic ligation of the hamartoma is that it is pediculated (15).…”
Section: A B C a Bmentioning
confidence: 99%
“…To the best of our knowledge, twenty studies with twenty esophageal hamartoma cases (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have been reported and eight of these studies described (4,6,8,10,11) were cervical or upper esophagus hamartomas [Halfhide et al (10) and Ginai et al (11) reported the same case], and five cases (5,7,9,13) were in distal or lower esophagus [one (9) was in Chinese, Table 1]. Several other studies (23-32) also reported congenital esophageal stenosis caused by tracheobronchial remnants.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the clinical manifestation and auxiliary examination were not specific, and EUS-FNA played an important role in preoperative diagnosis of the hamartoma. Xu et al (19) reported that EUS was superior to other imaging techniques, including barium esophagogram, contrast-enhanced CT image and conventional gastroscopy, in the diagnosis and treatment of hamartoma. Indeed, EUS can provide helpful diagnostic accuracy and comprehensive pre-operative assessment of submucosal tumors of the esophagus, including more detailed information about the tumor size, layer of origin, morphologic features, and even histopathological components (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation